Formulation and stability evaluation of 3D alginate beads potentially useful for cumulus–oocyte complexes culture. (17th February 2016) - Dorati, Rossella; Genta, Ida; Ferrari, Michela; Vigone, Giulia; Merico, Valeria; Garagna, Silvia; Zuccotti, Maurizio; Conti, Bice
Abstract: Ovarian follicle encapsulation in synthetic or natural matrixes based on biopolymers is potentially a promising approach to in vitro maturation (IVM) process, since it maintains follicle 3D organisation by preventing its flattening and consequent disruption of gap junctions, preserving the functional relationship between oocyte and companion follicle cells. The aim of the work was to optimise physico-chemical parameters of alginate microcapsules for perspective IVM under 3D environments. On this purpose alginate and cross-linking agent concentrations were investigated. Alginate concentration between 0.75% and 0.125% w/w and Mg 2+, Ba 2+, Ca 2+ at concentration between 100 and 20 mM were tested. Follicle encapsulation was obtained by on purpose modified diffusion setting gelation technique, and evaluated together with beads, chemical and mechanical stability in standard and stressing conditions. Beads permeability was tested towards albumin, fetuin, pyruvate, glucose, pullulan. Results demonstrated that 0.25% alginate cross-linked in 100 mM CaCl2 beads is suitable to follicle encapsulation.